Transmission of pancreatic adenocarcinoma by a single multiorgan donor to two kidney transplant recipients: A case report - Belčič Mikič, Tanja; Mlinšek, Gregor; Oblak, Manca; Kandus, Aljoša; Buturović-Ponikvar, Jadranka; Hawlina, Simon; Milanez, Tomaž; Kojc, Nika; Frelih, Maja; Arnol, Miha (Frontiers in Medicine, 2023)
We present two cases of transmission of a pancreatic adenocarcinoma from a single donor to two kidney transplant recipients. Autopsy of the donor revealed a pancreatic adenocarcinoma that had already spread locally to the regional lymph nodes and had not been detected at the time of organ procurement. Both recipients were carefully monitored, as neither consented to graft nephrectomy. In one patient, the tumor was discovered on surveillance biopsy of the graft approximately 14 months after transplantation, and in the second patient, ultrasound-guided aspiration needle biopsy of a growing formation in the lower pole of the graft revealed poorly differentiated metastatic adenocarcinoma. Both patients were successfully treated with graft nephrectomy and complete discontinuation of immunosuppression. None of the follow-up imaging showed persistent or recurrent malignancy, and both patients were candidates for re-transplantation. These exceptional cases of donor-derived pancreatic adenocarcinoma suggest that removal of the donor organ and restoration of immunity may lead to complete recovery.